Starting stiripentol in adults with Dravet syndrome? Watch for ammonia and carnitine. (21st October 2020) - Zulfiqar Ali, Quratulain; Marques, Paula; Selvarajah, Arunan; Tabarestani, Sepideh; Sadoway, Tara; Andrade, Danielle M.
Abstract: Objective: Dravet syndrome (DS) is a rare cause of severe and pharmacoresistant epileptic encephalopathy. Stiripentol (STP) has a significant therapeutic benefit in the pediatric DS population. However, STP effects on adult patients have not been well studied. In our adult STP‐naive DS patient population, STP initiation was associated with encephalopathy, despite decreases in valproate and clobazam dosage. Here we explored the cause and treatment of encephalopathic manifestations associated with STP in adults. Methods: Twenty‐eight patients with a confirmed clinical and genetic diagnosis of DS who attended the Adult Epilepsy Genetics Clinic were identified retrospectively. Patients who declined or discontinued STP after fewer than 3 months of use, patients who were deceased before starting STP or seizure‐free when the genetic diagnosis was confirmed, and those who started STP before leaving the pediatric system (<18 years) were excluded. Levels of ammonia, carnitine, and other anti‐epileptic drugs (AEDs) were observed for patients receiving STP. Patients with high ammonia levels who received carnitine supplementation were reevaluated. They were also offered an increased dosage of stiripentol if treatment with carnitine improved the encephalopathy. Results: We observed hyperammonemic encephalopathy in 77% of patients treated with STP. In seven of nine patients, we observed a rate of improvement in ammonia levels of 35% (95% confidence interval [CI] 21%–49%) at a mean carnitine dose of 991 ± 286 mg/d (range 660‐1320 mg/d). Five patients whose ammonia levels normalized were also offered an increase in STP dose and they were able to tolerate higher doses with improvement in side effects. Despite such adjustments, the mean maximum stiripentol dose reached was 14.89 ± 8.72 mg/kg/d, which is lower than what is typically recommended in children (50 mg/kg/d). Significance: We report hyperammonemia in adult STP‐naive patients who were on valproate and clobazam, despite dose reduction of the latter drugs. We also report that treatment with carnitine improved hyperammonemia, allowing the continuation of STP.